RETRACTED: Pre-training graph autoencoder incorporating hierarchical topology knowledge - Zhu, Hongyin; Li, Yakun; Liu, Luyang; Tong, Haonan; Lin, Qunyang; Zhang, Chuang (Expert systems with applications, 2025)
This article has been retracted: please see Elsevier policy on Article Correction, Retraction and Removal (https://www.elsevier.com/about/policies-and-standards/article-withdrawal). This article has been retracted at the request of the Author, with the approval of Expert Systems with Applications editor. Concerns were raised following the publication of the paper titled “Pre-training Graph Autoencoder Incorporating Hierarchical Topology Knowledge” (DOI: https://doi.org/10.1016/j.eswa.2024.125976) regarding undisclosed conflicts of interest and compliance risks. Specifically: 1. Unreported Conflict of Interests: The first author's affiliation at the time of publication, Qihoo 360, holds a conflict of interest with the institution, IEI. This conflict of interest was not disclosed during the submission or revision process, violating the journal's ethical guidelines on transparency. 2. Unauthorized Post-Acceptance Affiliation Changes: Following manuscript acceptance, the first author unilaterally altered their affiliation to Qihoo 360 without notifying or obtaining consent from other co-authors. This modification occurred after the peer-review process and contravenes the journal's policy requiring full disclosure of authorship changes. Considering these issues, the authors assert that the article no longer meets the standards of academic integrity, transparency, or compliance required by Expert Systems with Applications. The co-authors regret the necessity of this request and acknowledge the efforts of the editors and reviewers. Based on the evidence, the authors and the editor concluded that the article should be retracted.